Pengaruh Motivasi, Disiplin dan Kompetensi Kerja terhadap Kinerja Pegawai pada Dinas Lingkungan Hidup Kabupaten Batang Hari - Etty Siswati; Nadiatulkhoiroh Nadiatulkhoiroh (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
This study aims to determine the effect of (X1) Motivation, (X2) Work Discipline, (X3) Work Competence on (Y) Employee Performance pada Dinas Lingkungan Hidup Kabupaten Batang Hari. Day. This research is a quantitative descriptive study. The sample of this study was 53 people. Based on the results of research and discussion, then some of the main points of research conclusions can be explained as follows: Based on the results of the partial test (t test). Obtained tcount for (X1) Work Motivation of -0.272 and value of ttable of 1.67655 because tcount is smaller than ttable, it can be concluded that work motivation does not significantly influence employee performance. Whereas (X2) Work Discipline obtained tcount value of 5,542 and ttable value of 1.67655 because tcount is greater than ttable, it can be concluded that work discipline has a significant effect on employee performance. And for (X3) Work Competence obtained tcount of 3,805 and value of ttable of 1.67655 because tcount is greater than ttable, it can be concluded that work competence has a significant effect on employee performance. Based on the results of the Simultaneous Test (Test F). Obtained Fcount value of 75,665 and Ftable value of 2.79 because the Fcount value is greater Ftable, it can be concluded that work motivation, work discipline and work competence show a significant influence on employee performance. Based on the results of the Coofesien Determination (R2) obtained an Adjusted R Square value of 0.812 can be concluded the percentage influence of Work Motivation (X1), Work Discipline (X2) and Work Competence (X3) on Performance (Y) of 81.2% and 18.8% influenced by variables - other variables not examined in this study.